(untitled) (Research, Society and Development, 2020)
This work’s intention is to do a preliminary analysis of Dermeval Saviani’s works “School and Democracy” and “Historical-critical pedagogy: initial approaches” aiming to unveil the conception of Education built by the author, as well as its perspectives regarding the working class in the educational field. In this way, we used as methodological itinerary the comparative bibliographic research, sustained by the analytical categories of the historical materialism understanding the reality as a social construct. Saviani is one of the most important brazilian education theorists, and both of the works selected for this paper are literary classics about education. Dermeval over the last fifty years dedicated to this theme, developed a counter hegemonic idea of education focused on providing the working class with the necessary knowledge to understand the production process, as well as their formation as active citizens with a critical sense.